2015
DOI: 10.1007/s13277-015-3188-6
|View full text |Cite
|
Sign up to set email alerts
|

The elevated preoperative neutrophil-to-lymphocyte ratio predicts poor prognosis in intrahepatic cholangiocarcinoma patients undergoing hepatectomy

Abstract: A high preoperative peripheral blood neutrophil-to-lymphocyte ratio (NLR) has been reported to be a predictor of poor survival in patients with various cancers. The aim of this study was to evaluate the predictive significance of the NLR in patients undergoing hepatectomy for intrahepatic cholangiocarcinoma (ICC). From 2005 to 2011, 322 patients who underwent hepatectomy for ICC were enrolled in this retrospective study. Clinicopathological parameters, including NLR, were evaluated to identify predictors of ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 52 publications
4
63
1
1
Order By: Relevance
“…23 Elevated NLR is associated with worse survival after hepatectomy for intrahepatic cholangiocarcinoma. 24,25 Elevated preoperative NLR is associated with worse OS in gallbladder cancer at a lower threshold (>1.94) than the current study according to at least one other group of investigators. 26 Variables, p-values and hazard ratios in bold indicate those which were found to be significant on multivariate analysis.…”
Section: Discussionmentioning
confidence: 47%
“…23 Elevated NLR is associated with worse survival after hepatectomy for intrahepatic cholangiocarcinoma. 24,25 Elevated preoperative NLR is associated with worse OS in gallbladder cancer at a lower threshold (>1.94) than the current study according to at least one other group of investigators. 26 Variables, p-values and hazard ratios in bold indicate those which were found to be significant on multivariate analysis.…”
Section: Discussionmentioning
confidence: 47%
“…During the past decades, an increasing number of investigators focused on the relationship of inflammation with cancer prognosis. Inflammation-based scores including a combination of serum C-reactive protein and ALB as the Glasgow prognostic score were proven to be associated with survival in various cancers [14, 15, 24, 25]. It suggested that the ALB level might correlate with systematic inflammation [26].…”
Section: Discussionmentioning
confidence: 99%
“…Serum ALB levels could represent both systematic inflammation and nutritional status [13]. Systemic inflammation has been investigated to be involved in tumor progression and poor oncological outcome in various cancers [14, 15]. Moreover, preoperative nutritional status could affect survival in cancerous patients undergoing surgery [16].…”
Section: Introductionmentioning
confidence: 99%
“…NLR is an independent prognostic factor of survival in patients with upper gastrointestinal cancers and several types of solid organ malignancies (Walsh et al 2005;Jung et al 2011;Chen et al 2015;Duzlu et al 2015;Langsenlehner et al 2015;Okamura et al 2015;Song et al 2015;Szkandera et al 2015;Ji et al 2016). However, there are a few studies regarding the thyroid cancers.…”
Section: Discussionmentioning
confidence: 99%